Isolation and identification of cellulose decomposition bacteria from the soil of Yunnan province, China (Bangladesh Journal of Botany, 2024)
In this experiment sodium carboxymethyl cellulose (CMC-Na) was used as the only carbon source to isolate cellulose decomposing bacteria from the soil of Qiongzhusi Forest Park in Kunming, Yunnan Province. The ratio of hydrolytic circle diameter and colony diameter formed by the strain on cellulose Congo red medium was determined for primary screening, and then the filter paper disintegration test and CMC enzyme activity assay were used for rescreen. A cellulose decomposing bacterium (HS-2) with high enzyme activity was obtained, and its enzyme activity was up to 16.42 U/ml. (U means the unit of activity of enzymes, activity, unit) Gram stain and Spore stain reaction showed that HS-2 strain was Gram-positive Bacillus. The Bacillus strain was identified as Bacillus pumilus on the basis of physiological and biochemical tests, and 16S rDNA sequence analysis.Bangladesh J. Bot. 52(3): 635-641, 2024 (September) Special